2014
DOI: 10.1159/000367685
|View full text |Cite
|
Sign up to set email alerts
|

Reduced N-Acetylaspartate to Creatine Ratio in the Posterior Cingulate Correlates with Cognition in Alzheimer's Disease following Four Months of Rivastigmine Treatment

Abstract: Aim: To determine whether 4 months of rivastigmine treatment would result in metabolic changes and whether metabolic changes correlate with changes in cognition in people with Alzheimer's disease (AD). Methods: Magnetic resonance spectra were acquired from the posterior cingulate cortex of subjects with AD at 3 T. Magnetic resonance imaging scans and cognitive tests were performed before and 4 months after the beginning of the treatment. Metabolite concentrations were quantified and used to calculate the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…When NAA declines in the brain, nervous functional impairment may develop ( 22 , 23 ). Previous studies demonstrated that the NAA level is positively correlated with learning and memory in different diseases ( 24 , 25 ), whereas a higher ratio of NAA/Cr is accompanied with better Mini-Mental State Examination scores in Alzheimer's disease ( 26 ). Moreover, Cho is an important neurotransmitter precursor compound of acetylcholine, which is related to memory, recognition and emotional behavior ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…When NAA declines in the brain, nervous functional impairment may develop ( 22 , 23 ). Previous studies demonstrated that the NAA level is positively correlated with learning and memory in different diseases ( 24 , 25 ), whereas a higher ratio of NAA/Cr is accompanied with better Mini-Mental State Examination scores in Alzheimer's disease ( 26 ). Moreover, Cho is an important neurotransmitter precursor compound of acetylcholine, which is related to memory, recognition and emotional behavior ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researches had been demonstrated that NAA and NAA/Cr were significantly decreased in the hippocampus or cortex in APP/PS1 double transgenic mice, and it was thought to be associated with deletion of neuronal cells [ 30 ]. Besides, Oberg had been shown that compared with 6–9 months old WT mice, Glu had a significantly reduced in APP/PS1 double transgenic mice [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its potential clinical significance arises from the fact that NAA has been shown to be important in neuronal function, Singhal et al (2017) such that decreased NAA has been shown to be related to neuronal damage (Wagner et al, 2013) and reduced structural brain volume in neurological disease (Cohen et al, 2010). Further, decreased levels of NAA are associated with impaired neuronal function, cognition (Paul et al, 2016) and a variety of brain disorders that affect cognition (Penner et al, 2015;Cysique et al, 2018). MI plays an important role in insulin signaling (Jones and Varela-Nieto, 1999), intracellular calcium regulation (Berridge and Irvine, 1989), the cytoskeleton assembly (Janmey et al, 1999), fat breakdown (Plows et al, 2017), and cell membrane maintenance (Shewan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%